2018
DOI: 10.1182/blood-2018-05-850727
|View full text |Cite
|
Sign up to set email alerts
|

IMiDs prime myeloma cells for daratumumab-mediated cytotoxicity through loss of Ikaros and Aiolos

Abstract: Abstract Recent studies have demonstrated that the immunomodulatory drugs (IMiDs) lead to the degradation of the transcription factors Ikaros and Aiolos. However, why their loss subsequently leads to multiple myeloma (MM) cell death remains unclear. Using CRISPR-Cas9 genome editing, we have deleted IKZF1/Ikaros and IKZF3/Aiolos in human MM cell lines to gain further insight into their downstream gene regulatory networks. Inactivation of either factor alone recapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 59 publications
5
70
0
Order By: Relevance
“…On the other hand, lenalidomide potentiated DARA-induced ADCC against MM cells by directly stimulating NK cells without modifying CD38 expression on these cells. Overall these evidences indicate that the clinical synergistic effect of the combination of lenalidomide and DARA is likely due either to the increased CD38 expression on MM cells or to the stimulation of NK activity [52].…”
Section: Drug-mediated Modulation Of Cd38 Expression By MM Cellsmentioning
confidence: 88%
See 4 more Smart Citations
“…On the other hand, lenalidomide potentiated DARA-induced ADCC against MM cells by directly stimulating NK cells without modifying CD38 expression on these cells. Overall these evidences indicate that the clinical synergistic effect of the combination of lenalidomide and DARA is likely due either to the increased CD38 expression on MM cells or to the stimulation of NK activity [52].…”
Section: Drug-mediated Modulation Of Cd38 Expression By MM Cellsmentioning
confidence: 88%
“…In particular, CD38 was up regulated after IMiDs treatment whereas ITGA8 and ICAM2 (CD102) were both down-regulated [51]. More recently, Fedele P. et al [52] reported that lenalidomide treatment increases CD38 expression in several human myeloma cell lines, through Ikaros and Aiolos degradation. Thereafter, the authors tested the hypothesis that the additive effect observed by the combination of anti-CD38 mAbs and IMiDs in vitro could be due to the upregulation of CD38 by IMiDs [52].…”
Section: Drug-mediated Modulation Of Cd38 Expression By MM Cellsmentioning
confidence: 99%
See 3 more Smart Citations